2014
DOI: 10.1038/ncomms4061
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic inhibition of socio-sexual behaviour by increasing neuroestrogen synthesis

Abstract: Gonadotropin-inhibitory hormone (GnIH) is a hypothalamic neuropeptide that inhibits gonadotropin secretion and socio-sexual behaviours. Oestrogen (neuroestrogen) synthesized in the brain from androgen by aromatase regulates male socio-sexual behaviours. Here we show that GnIH directly activates aromatase and increases neuroestrogen synthesis in the preoptic area (POA) and inhibits socio-sexual behaviours of male quail. Aromatase activity and neuroestrogen concentration in the POA are low in the morning when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 63 publications
1
112
0
2
Order By: Relevance
“…The follow-up studies demonstrated that GnIH is highly conserved among vertebrates, from agnathans to humans, and that it acts as a key player for regulation of reproduction (for reviews, see Kriegsfeld et al, 2015;Tsutsui, 2009;Tsutsui and Ubuka, 2012;Tsutsui and Ukena, 2006;Tsutsui et al, 2006bTsutsui et al, , 2007Tsutsui et al, , 2010aTsutsui et al, ,b, 2012bTsutsui et al, , 2013dUkena and Tsutsui, 2005). In addition, recent studies have demonstrated that GnIH has other important functions beyond reproduction Ubuka et al, 2014). It now appears that GnIH acts on the pituitary and the brain to serve a number of behavioral and physiological functions other than regulation of reproduction.…”
Section: Overviewmentioning
confidence: 95%
See 1 more Smart Citation
“…The follow-up studies demonstrated that GnIH is highly conserved among vertebrates, from agnathans to humans, and that it acts as a key player for regulation of reproduction (for reviews, see Kriegsfeld et al, 2015;Tsutsui, 2009;Tsutsui and Ubuka, 2012;Tsutsui and Ukena, 2006;Tsutsui et al, 2006bTsutsui et al, , 2007Tsutsui et al, , 2010aTsutsui et al, ,b, 2012bTsutsui et al, , 2013dUkena and Tsutsui, 2005). In addition, recent studies have demonstrated that GnIH has other important functions beyond reproduction Ubuka et al, 2014). It now appears that GnIH acts on the pituitary and the brain to serve a number of behavioral and physiological functions other than regulation of reproduction.…”
Section: Overviewmentioning
confidence: 95%
“…GnIH participates not only in neuroendocrine functions but also in behavioral mechanisms because it decreases sexual behavior and stimulates feeding behavior in birds McConn et al, 2014;Tachibana et al, 2005Tachibana et al, , 2008Ubuka et al, 2012bUbuka et al, , 2014. Recently, we have demonstrated multiple functions of GnIH by GnIH RNA interference, RNAi in quail .…”
Section: Multiple Actions Of Gnihmentioning
confidence: 95%
“…Aromatase activity and gene expression within the brain is differentially regulated in distinct neural regions linked to social and reproductive behavior, where E 2 exerts a local effect (Dickens et al, 2014;Huffman et al, 2013;Remage-Healey et al, 2008;Ubuka et al, 2014). Thus, treatment with an aromatase inhibitor impairs E 2 synthesis in all brain regions, including local regulatory niches of aggressive behavior.…”
mentioning
confidence: 94%
“…Recent approaches now allow the measurement of the on-line activity and neurochemical state of cognitive circuits. Relevant to the current topic, in vivo central E2 measurements have provided direct information about physiological changes in local steroid environments, and have been successfully adapted for songbirds [51], quail [52], rats [53], and nonhuman primates [54]. Studies using in vivo microdialysis, as well as brain content assays of macroarea homogenates, have revealed that E2 synthesis is elevated following recent learning events [51,55].…”
Section: Introductionmentioning
confidence: 99%